Mediating role of learning goal orientation and predictors of job satisfaction among caregivers of people with disability in Selangor, Malaysia - Abdul Rahman, Segufta Yasmi (2022)
Job satisfaction is an important element for the field of HRD through organizational development. The main objective of the HRD field is to unleash human expertise through employees' capabilities that benefit the organization. Meanwhile, job satisfaction is the response of employees to their work that affects their productivity and organizational development. Although in recent years, studies associated with job satisfaction have started to proliferate, the mediating effect of learning goal orientation on the relationship between the individual differences factors (self-efficacy, personality traits), work condition and outcome factors (expectancy outcome, perceived organizational support, job autonomy), and job satisfaction has been poorly understood. Moreover, less focus is given to the caregivers of people with disability. Therefore, to bridge this gap and gain new insight, this study aims to examine the role of the mediation effect of learning goal orientation and the selected factors that influence job satisfaction among caregivers of people with disability. This study theorised job satisfaction using the Model of Work Satisfaction by Lent and Brown (2006) as the main underpinning theory and integrating it with the Model of Proactive Behavior by Crant (2000) to explain job satisfaction among caregivers with disability in Selangor. This study used a quantitative approach with a correlation research design. In addition, it adopted a cross-sectional study design using a structured questionnaire for data collection. The study sample consisted of a total of 325 caregivers of people with disability from the Community Base Rehabilitation Center (CBR) in Selangor, Malaysia, selected through cluster sampling and purposive sampling. Their answers were analyzed descriptively to determine the level of all continuous variables involved. Structured Equation Modelling (SEM) is used for hypotheses testing. Descriptive statistical analysis showed that levels of job satisfaction, individual differences factors (self-efficacy, personality traits), work condition and outcome factors (expectancy outcome, perceived organizational support, job autonomy) and learning goal orientation are moderate. The results of the study found that there are strong relationships between individual differences factors (self-efficacy and personality traits), work condition and outcome factors (expectancy outcome, perceived organizational support and job autonomy), learning goal orientation and job satisfaction. Selfefficacy, expectancy outcome and job autonomy influence job satisfaction, while no influence was shown by personality traits, perceived organizational support and learning goal orientation on job satisfaction. Finally, the study showed no mediating effect of learning goal orientation between all predictors and job satisfaction. Overall, the study shows caregivers of people with disability are aware of the importance of job satisfaction. HRD practitioners must enhance their role in the organization by raising awareness of the importance of having a desire to learn in order to increase their knowledge and skills for the purpose of organizational development. Self-efficacy is the most influential factor on job satisfaction among caregivers with disability, as it is the primary determinant of their continued survival in the organization.